Meme Politik Sebagai Representasi Komunikasi Kritis Di Media Sosial - Suryana Putra, Adnan; Rizka Aditriyana, Muhamad; Sri Widya , Novia; Fachrul Nurhadi, Zikri (CV RIFAINSTITUT, 2023)
Towards the 2024 election, supporters and critics of the presidential candidates have emerged, with critics using social media as a tool to communicate their criticism to the candidates through political memes as a form of their critical efforts. This research aims to examine the role of political memes as representations of critical communication on Facebook, targeting the presidential candidates in 2024. This study employs a qualitative method, adopting Charles Sanders Pierce's semiotic theory. The research selects political memes that highlight the 2024 presidential candidates on Facebook. Data collection techniques used include observation, interviews, and literature review. The collected meme data will be analyzed using Pierce's semiotic approach to understand how the images and texts in the memes contribute to constructing criticism towards the presidential candidates. The results of this research demonstrate that political memes serve as effective communication tools for expressing political criticism. The context conveyed by memes does not always represent the character of the criticized candidates, but they are capable of directing attention to the issues deemed important by the meme creators. The use of images and texts in the construction of criticism in memes plays a significant role in shaping the interpretation by the audience. This interpretation is also influenced by the audience's knowledge of the presented meme context.